The Effectiveness Of Citric Acid As An Anti-Ectoparasite Of Marine Leech (Zeylanicobdella arugamensis) Through Soaking - Nike Mustika Sari; Gede Iwan Setiabudi; Indah Mastuti; Ketut Mahardika (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2023)
Zeylanicobdella arugamensis infection causes health problems for cultured grouper. This study aims to determine the effectiveness of citric acid soaking as an anti Z. arugamensis ectoparasite. A total of ±120 Z. arugamensis were isolated from sick hybrid grouper (Epinephelus fuscoguttatus x E. lanceolatus) placed in Petri dishes (6 Petri dishes). Citric acid solution with 0, 50, 100, 150, 250, and 400 ppm was added to the petri plates. Immersion of Z. arugamensis was carried out for 30, 60, 90 and 120 minutes. Each 30 Z. arugamensis/treatment/30 minutes was taken and placed in 3 petri dishes (10 individuals/petri dish) filled with seawater. Observations were made on the response of Z. arugamensis. Comments were made on cocoon development into larvae. The citric acid safety test was conducted on cantang hybrid grouper infected with Z. arugamensis. A total of 3 test fish were soaked with citric acid solution in seawater at concentrations of 0, 150, 250, and 300 ppm. Observations of fish condition were made after 30 and 60 minutes of immersion. The results showed that citric acid concentrations of 250 and 400 ppm effectively killed Z. arugamensis (76.67±15.28-100%), and their cocoon development reached (0%). A citric acid concentration of 300 ppm is still safe to use for immersion of cantang hybrid grouper infected with Z. arugamensis for 60 minutes. Citric acid concentrations of 250-300 ppm can also release Z. arugamensis from the fish body. Citric acid has antiparasitic properties and lowers the pH of seawater.